2003
DOI: 10.1063/1.1613637
|View full text |Cite
|
Sign up to set email alerts
|

Quasielastic neutron scattering characterization of the relaxation processes in a room temperature ionic liquid

Abstract: The first example of QENS data from a room temperature ionic liquid, 1-n-butyl-3-methylimidazolium hexafluorophosphate, over the temperature rnage 250 to 320 K was reported using a medium resolution spectrometer. These data were used to derive the intermediate incoherent dynamic structure factor. The data indicate that the existence of two different relaxation processes occurring in the sample over the probed time/temperature ranges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
122
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 41 publications
13
122
0
Order By: Relevance
“…Wide-angle X-ray scattering results on the [C 4 mim][I] room temperature ionic liquids show prominent peaks in the residual radial distribution curve [118], indicating certain periodical arrangements of the iodide anions. The existence of different rotamers and local structures has also been found by interpretation of results from optical heterodynedetected Raman-induced Kerr-effect spectroscopy (OHD-RIKES) [139], from neutron scattering and diffraction experiments versus temperature [111][112][113]140], from Coherent anti-Stokes Raman Scattering (CARS) [141] and by theoretical molecular dynamics calculations [43,47,[142][143][144]. The local structures may also lead to other unique properties of ionic liquids; for example, if magnetic anions are aligned in RTILs, novel magnetic liquids will be created [145,146].…”
Section: Conformational Equilibria In Liquids Versus Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Wide-angle X-ray scattering results on the [C 4 mim][I] room temperature ionic liquids show prominent peaks in the residual radial distribution curve [118], indicating certain periodical arrangements of the iodide anions. The existence of different rotamers and local structures has also been found by interpretation of results from optical heterodynedetected Raman-induced Kerr-effect spectroscopy (OHD-RIKES) [139], from neutron scattering and diffraction experiments versus temperature [111][112][113]140], from Coherent anti-Stokes Raman Scattering (CARS) [141] and by theoretical molecular dynamics calculations [43,47,[142][143][144]. The local structures may also lead to other unique properties of ionic liquids; for example, if magnetic anions are aligned in RTILs, novel magnetic liquids will be created [145,146].…”
Section: Conformational Equilibria In Liquids Versus Temperaturementioning
confidence: 99%
“…Although other techniques such as infrared spectroscopy, X-ray, and neutron diffraction studies have been used to study these ions in the liquid or solid state or at surfaces [6,52,[109][110][111][112][113][114][115][116][117][118][119][120], a real gain in our understanding came with the combination of crystal structure solution, Raman spectroscopy and ab-initio DFT calculations [108,121]. We concentrate the story on the instructive example of the l-butyl-3-methylimidazolium cation, [C 4 mim] þ (see Fig.…”
Section: Brief Introduction To Ab-initio Model Calculationsmentioning
confidence: 99%
“…In order to clarify the above mentioned complex interplay one may study a plethora of physical properties, either with experiments [10][11][12][13][14][15][16][17][18] or simulations. 19 However, it is reasonably expected that the combination of both approaches will give a deeper insight [20][21][22][23] as on the one hand, simulations are able to decompose a physical property into contributions associated specifically with the cations, the anions and the coupling of both.…”
Section: Introductionmentioning
confidence: 99%
“…The butyl chain for the imidazolium ring shows the minimum in the melting temperatures [13,15], but most important, bmim based RTIL are known to be easily supercooled. In particular, a quasielastic neutron scattering study of 1-butyl-3-methylimidazolium PF 6 (bmim-pf 6 ) showed the existence of two relaxation processes, the slower one showing the characteristics typical of the glass transition dynamics [17].…”
mentioning
confidence: 99%
“…The butyl chain for the imidazolium ring shows the minimum in the melting temperatures [13,15], but most important, bmim based RTIL are known to be easily supercooled. In particular, a quasielastic neutron scattering study of 1-butyl-3-methylimidazolium PF 6 (bmim-pf 6 ) showed the existence of two relaxation processes, the slower one showing the characteristics typical of the glass transition dynamics [17].Among all the available cations that form ionic liquids, we chose to study the family of bmim derivatives due to their property of being easily supercooled. In this work we study the dynamics of a series of RTIL based on the same bmim cation and different anions: chloride (cl), hexafluorophosphate (pf6), trifluoromethane sulfonate imide (msf), bis(trifluoromethane sulphonate)imide (bmsf) in the temperature range from 400 K down to 10 K. Differential scanning calorimetry (DSC) is used to detect phase transitions of the samples and to extract the calorimetric glass transition temperature T g .…”
mentioning
confidence: 99%